Lower Cretaceous Fossil Site near Leše: First Heteromorphic Ammonoid Site in Slovenia and Karawanken/Karavanke UNESCO Global Geopark - Matija Križnar; Darja Komar; Mojca Bedjanič; Gerald Hartmann; Aljoša Šafran; Ivan Ocepek (Geoconservation Research)
The cross-border Geopark Karawanken/ Karavanke was established in 2011 to reflect the diverse geological composition and varied and rich natural and cultural heritage of the area. The wealth of geological heritage is reflected in numerous, already existing geosites, exceptional and unique on a global level, as well as in newly determined mineral and fossil sites. An example of the latter is the fossil site with rare Valanginian-Hauterivian heteromorphic ammonites, located in the SE part of the Karawanken/ Karavanke UNESCO Global Geopark, near Leše village above Prevalje. It is the first and newly discovered locality of heteromorphic ammonites Himantoceras trinodosum Thieuloy, 1964 and Crioceratites cf. nolani Kilian, 1910 in Slovenia. We explore the importance and potential of good cooperation between the local community, paleontologists and other geoscientists, geoheritage (paleontological heritage) conservation and UNESCO Global Geoparks.